The impact of oil-market shocks on stock returns in major oil-exporting countries. (September 2018) - Basher, Syed Abul; Haug, Alfred A.; Sadorsky, Perry
Highlights: Analysis of effects of oil price shocks on stock markets in oil exporting countries. Use of a structural VAR for the oil market. Oil price shocks are relevant for constructing portfolios for investors. Using Markov-switching probabilities can outperform a buy and hold strategy. Abstract: The impact that oil-market shocks have on stock prices in oil exporting countries has implications for both domestic and international investors. We derive the shocks driving oil prices from an oil market model that explicitly identifies speculative trading in the crude oil market. We study the nonlinear relationship of oil price shocks with stock market returns in major oil-exporting countries in a multi-factor Markov-switching framework. Flow oil-demand shocks have a statistically significant impact on stock returns in Canada, Norway, Russia, Kuwait, Saudi Arabia, and the UAE. Idiosyncratic oil-market shocks affect stock returns in Norway, Russia, Kuwait, Saudi Arabia and UAE. Speculative (oil-inventory) shocks impact stock returns in Canada, Russia, Kuwait and the UAE. Flow oil-supply shocks matter for the UK, Kuwait, and UAE. Mexico is the only country where stock returns are unaffected by oil-market shocks. A portfolio that uses the Markov-switching probabilities to switch between equities in the low volatility state and T-bills in the high volatility state outperforms a buy and hold strategy for some countries.